Potensi Buah Adas (Foeniculum vulgare) sebagai Gastroprotektor - Mira Yustika Susilo (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Gastritis is an inflammatory process that occurs in either the mucosa or submucosa in the stomach. The inflammation process can be caused by various things namely infection or irritant irritants. The utilization of traditional ingredients as prevention of gastritis is growing because it is considered to have more minimal side effects. The most common use of traditional ingredients is the antioxidant content of plants. One of the plants that has antioxidant compounds that are easy to find in Indonesia is fennel fruit (Foeniculum vulgare). Utilization of fennel in the health sector is related to its high content of organic acids, proteins, choline, trigonelline, and antioxidants in the form of flavonoids which can prevent the occurrence of lipid peroxidation mechanisms caused by oxidative stress.